Becoming secular, yet remaining religious: the Gülen movement and the 'engineering' of the golden generation. Issue 1 (2nd January 2021) - Tittensor, David
ABSTRACT: In recent years there has been a religious turn in the development sector with the World Bank and national funding agencies in Europe and the US opening the space to Faith Based Organisations (FBOs). However, for some Islamic FBOs, this has not led to a comfortable assertion of their religious identity and mission on the world stage. Rather, in the post 9/11 environment, some Islamic FBOs have opted to develop an 'invisible Islam' wherein they background their religion through secularizing their language with a view to better integrating into the normative aid sector. Drawing on the work of Marie Juul Petersen and reflecting on the author's own fieldwork on the Gülen Movement (GM), this paper will unpack this development. In doing so, it will highlight that the practice by GM is only a semantic exercise to cover its ongoing religious mission on account of continued hostility towards Islamic actors.